2000
DOI: 10.1063/1.372085
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometric study of polycrystalline silicon films prepared by low-pressure chemical vapor deposition

Abstract: Polysilicon layers with thicknesses between 8 and 600 nm deposited by low-pressure chemical vapor deposition at temperatures ranging from 560 to 640°C were characterized by spectroscopic ellipsometry ͑SE͒ to determine the layer thicknesses and compositions using multilayer optical models and the Bruggeman effective-medium approximation. The dependence of the structural parameters on the layer thickness and deposition temperature have been investigated. A better characterization of the polysilicon layer is achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…3). The higher the volume fraction of the nc-Si component, the smaller the grain size [25]. The sensitivity is revealed to be high, however, quantitative measurements verified by reference methods were not performed.…”
Section: Measurable Nanocrystal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The higher the volume fraction of the nc-Si component, the smaller the grain size [25]. The sensitivity is revealed to be high, however, quantitative measurements verified by reference methods were not performed.…”
Section: Measurable Nanocrystal Propertiesmentioning
confidence: 99%
“…2 (see also Ref. [25]). The surface nanoroughness is also considered as a homogeneous layer [9], the thickness of which correlates with the root mean square roughness [22].…”
Section: Measurable Nanocrystal Propertiesmentioning
confidence: 99%
“…Though contradictions still exist regarding the choice of a particular effective medium model over another and in actual interpretation of the thickness of the surface layer in the context of surface height irregularities, the above approach has been used quite successfully in many cases, particularly in characterization of surfaces of semiconductors ͑herein, p-type diamond͒. 20,21 The SE results are critically examined with other techniques measuring surface properties such as atomic force microscopy ͑AFM͒. Since SE measures the optical or dielectric constants, those results can also be corroborated with electrical C-V measurements and electrostatic force microscopy modeling.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The effect of the microstructure on the optical properties is an important issue for both an in situ characterization of material growth and a clarification of electronic properties. The optical characteristics of structurally inhomogeneous semiconductor such as c-Si:H has been interpreted simply as an effective medium of the two-phase ͑or three-phase͒ materials [3][4][5] although such a microstructure may cause internal light scattering. 6,7 It is found that the silane concentration SC ͑gas flow ratio ͓SiH 4 ͔/͓SiH 4 ϩH 2 ͔͒ is the most common parameter to control the structure of the material prepared by plasmaenhanced chemical-vapor deposition ͑PECVD͒ and the crystalline volume fraction ( f c ) decreases with increasing SC.…”
Section: Introductionmentioning
confidence: 99%